Knowledge-intensive consumer services. Understanding KICS in the innovative global health-care sector - Costa, C. M.; Mendonça, S. (Research Policy, 2019)
This paper explores a case of knowledge-intensive consumer services (KICS). Services have become less neglected in the economics of technical change and innovation studies in general; nevertheless, the advance of this agenda has been uneven. A significant emphasis has been on knowledge-intensive business services (KIBS). Despite their direct impact on social needs and individual desires, innovation in consumer-oriented services continues to be relatively under-theorized and under-researched. This paper brings into focus the sources and patterns of innovation in those innovative services that target human satisfaction and well-being as a final goal. We show evidence from a little-explored health industry, oral care. We address Malo Clinic, a company specialized in the most complex patient situations and a rare instance of an internationalized firm in the health services business. On the basis of a 20-year thread of corporate history, we find that a wide array of qualitative (interviews, newspaper coverage, marketing material) and quantitative evidence (papers, patents, trademarks) illuminates some of the features that may characterize a particular class of dynamic activities tending to consumers’ needs, expectations and quality of life. We argue that these key characteristics may be on course to become more general as the learning economy spreads to fully embrace the realm of the service sphere. One conclusion is that both the technological and non-technological capabilities underpinning more types of innovation are increasingly becoming coupled in consumer-relevant services.